Ultrasonographic evaluation of ovarian morphology and blood flow in prepubertal and pubertal cats - Vercellini, María del Rosario (2018)
The aim of this study was to evaluate two‐dimensional and Doppler ultrasonographic changes of feline ovaries before and during puberty. Nine, 3‐month‐old female cats were followed until puberty (Day 1). Two‐dimensional and Doppler ultrasound evalu‐ ations of the ovaries were carried out on Days ‐50, ‐20, ‐7 and 1. Longitudinal and transverse sections of the ovaries were measured and all anechoic spherical struc‐ tures were considered to be follicles. The number of follicles >1 mm and the maxi‐ mum diameter of the largest follicle were recorded. Peak systolic velocity and end diastolic velocity of intraovarian arteries were also measured to automatically calcu‐ late the resistive index (RI). The mean ovarian longitudinal diameter increased gradu‐ ally throughout the study from 8.6 to 10.7 mm (p < 0.05). While four cats presented multiple anechoic spherical structures <1 mm diameter throughout the study, the remaining five animals had these structures only on Days ‐50 and ‐20. On Days ‐20, ‐7 and 1, the mean number of follicles were 1.4 ± 0.7, 2.5 ± 0.8 and 4.8 ± 1 respec‐ tively (p < 0.01). The largest follicles at the same time points were 1.1 ± 0.2 mm, 1.9 ± 0.3 mm and 2.6 ± 0.5 mm respectively (p < 0.05). The RI of the intraovarian ar‐ teries declined throughout the study period (p < 0.01). It is concluded that, in female cats, ovarian dimensions, follicle number and intraovarian blood flow increased from 3 months of age to puberty.